Sistematik Review: Peran Media Sosial dalam Pemasaran Media Sosial Selama Covid - 19 - Istiqomah, Amalia Risni; Indriastuti, Noviana; Nggona, Jenike Bangu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Covid-19 pandemic has driven a lot of transformation in several fields, including in social media marketing strategies for UMKM. This study aims to identify the implementation of the use of social media marketing (SMM), especially representation and engagement tactics, in supporting the sustainability of UMKM during the Covid-19 pandemic. This analysis uses a systematic literature review approach. Where 5 journals used are indexed by Science Direct, Google Scholar, SINTA. The results of the analysis indicate that social media is a very effective means of building a company's image.